National antibiotic consumption for human use in Chad (2017–2021): a descriptive cross-sectional study - Frank Edgard, Zongo R.; Traoré, Kadidjia Bakari; Ngabéré, Colette; Yoyammel, Martine; Kadai, Abatcha Oumar; Efobi, John Eyong; Hota, Mathieu; Lamireou, Didi; Mahamat, Badawi Haroun; Alio, Hamit Mahamat; Tamuzi, Jacques L.; Katoto, Patrick D. M. C.; et al. (Frontiers in Antibiotics, 2025)
BackgroundAntibiotic resistance (ABR) to commonly used antibiotics is significant in sub-Saharan Africa (SSA). In SSA, Chad has one of the highest antimicrobial resistance (AMR) rates. The link between ABR and antibiotic consumption (ABC) is well-established. However, no ABC-related studies have been conducted in Chad recently. The purpose of this study is to examine the trajectory of ABC in Chad from 2017 to 2021, using the World Health Organization’s (WHO) Access, Watch, and Reserve (AWaRe) antibiotic classification.MethodsA descriptive retrospective study was conducted in N’Djamena, using antibiotic import and distribution data collected from the General Directorate of Pharmacy and four wholesale distributors of medicines. The defined daily doses (DDDs) and the mean relative change (MRC) were used to compute the results. Results were presented in terms of tables and graphs. The results were compared to the WHO’s guidelines for ABC use via the AWaRe categorization.ResultsBetween 2017 and 2021, an average ABC of 2.5 doses per inhabitant per year was observed, peaking in 2020 at 5.3 doses per inhabitant. In terms of DDD, the ten most commonly consumed antibiotics during the time, in descending order, were amoxicillin, ampicillin, sulfamethoxazole/trimethoprim, doxycycline, ciprofloxacin, phenoxymethyl-penicillin, erythromycin, ceftriaxone, azithromycin, and gentamicin. However, the MRC analysis detected an increase in benzathine benzyl penicillin, benzylpenicillin, ampicillin, amoxicillin+clavulanic acid, flucloxacillin, ceftriaxone, cefixime, cefpodoxime and cefalexin, cotrimoxazole, ciprofloxacin, levofloxacin, norfloxacin, ofloxacin, and azithromycin. Controversially, amoxicillin, cefotaxime, doxycycline, erythromycin, and moxifloxacin had a lower MRC from 2017 to 2021. Although 90% of the ABC are from the “Access” group, the “Watch” group has increased over time.ConclusionsOur findings indicated a significant ABC in the Chadian population from 2017 to 2021, which may elucidate the country’s elevated ABR. On average, 90% of ABC were categorized in the “Access” group, although utilization of the Watch group increased over time. This requires the prompt implementation of the monitoring system for ABC at all tiers in Chad.